KEMAMPUAN LITERASI MATEMATIKA PESERTA DIDIK DALAM MENYELESAIKAN SOAL HIGHER ORDER THINKING SKILL (HOTS) - Nining Setyaningsih; Siti Fatimah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The development of information and communication technology has an impact on the need for innovative resources and is able to solve problems properly. This makes education an important thing to pay attention to and one of them is with mathematics subjects. One of the focuses in mathematics is the HOTS problem where in its application and work, each student is different. The purpose of this study is to describe the ability of mathematical literacy in solving HOTS problems. The method used in this study is qualitative with data tringaluation. The stage of this study is the collection of data as a whole using two questions that are shared with all students and supported by interviews. The results of this study show that overall mathematical literacy skills in students, the use of HOTS-type mathematics problems in mathematics learning is able to achieve mathematical literacy indicators. However, the mathematical literacy ability in students is different, namely male students have better literacy than female students in solving HOTS problems. Male students can solve problems completely and in sequence, while female students are less coherent in doing the questions.